ON-LINE EVALUATION OF TYPES OF CROWNS USED IN CLINICAL PRACTICE OF DENTAL STUDENTS AT AN INTERNATIONAL LEVEL - Anca Vitalariu; Ionut Luchian; Diana Diaconu; Monica Tatarciuc (Romanian Journal of Oral Rehabilitation, 2013)
Continuous development of technology in dental medicine and the high esthetic demands of the patients determined a significant increase of using non-metallic crowns in clinical practice of dental students. Zirconium, pressed ceramics or CAD-CAM technologies seems to become part of the daily routine in the dental faculties creating a tendency of replacing the classical solutions. Matherial and Method. We used an on-line survey with questions regarding the frequency of using different types of crowns by dental students and also regarding the use of different impression materials and cementation protocols. The questionnaire was set using an electronic platform and a special data base able to register the answers. The survey was sent to dental students from 42 different countries using the logistics of the International Association of Dental Students (IADS). Results. The results shown that the frequency of using different types of crowns in clinical practice was different and connected to the therapeutic concepts of the dental school they study in, to the country they live in and to the social and economical status of the geographical area. Conclusions. The full ceramic crowns and zirconium based crowns had a high frequency of using especially in the anterior area. The use of the noble alloys as metallic frame was not that popular. The study also put into evidence the inappropriate use of the luting materials for the full ceramic and zirconium based crowns in some cases.